PEMBELAJARAN BAHASA BERBASIS TEKS DALAM KURIKULUM 2013 - Amrin Saragih (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Language learning in the curriculum in 2013 based on the text. Steps or stages in the cycle of text-based learning is consistent and aligned with the learning based on a scientific approach which characterizes the Curriculum 2013. Kesejalanan and alignment of the text-based learning supports the achievement of integrative knowledge, skills and attitudes that the distinguishing feature Curriculum 2013 and the previous curriculum. Furthermore, the text-based learning in the curriculum in 2013 the role of natural language as a draft or perealisasi science in the form of grammar or leksikogramar strengthened. Thus, the role of language learning across subjects is in line with the globalization paradigm in science.